Evaluation of Adverse Drug Reaction Profile of Drugs Used as First-Line Antiretroviral Therapy. (2nd August 2018) - Chowta, Mukta N.; Kamath, Priyanka; Ramapuram, John T.; Shenoy, K. Ashok; Hadigal, Sanjay
Abstract : Background and Objectives. The objective was to study the adverse drug reaction (ADR) profile in HIV patients receiving first-line antiretroviral therapy. Methods. This was a prospective, observational study that included 171 HIV patients with a follow-up at six months. Demographic details, medical history, details of HIV infection including most recent CD4 count, details of antiretroviral therapy, and other concomitant medication were recorded. Adverse drug reactions were elicited by reviewing patient records and also by interviewing the patient/attendants directly. Results. 171 patients completed the study out of which 88 (51.5%) were males and 83 (48.5%) were females. The study subjects included HIV-positive, treatment naïve patients who were started on treatment regimens recommended by the NACO guidelines. The ADRs observed were a fall in haemoglobin or absolute anaemia in response to zidovudine, nonspecific symptoms like headache, and a nonspecific feeling of being unwell in response to tenofovir, stavudine, and efavirenz; dyslipidaemia, pancreatitis, peripheral neuropathy, and lactic acidosis in response to stavudine; generalised rash in response to nevirapine and one case of nephrotoxicity to efavirenz. Majority of the ADRs satisfied the 'probable' category (60.1%), and the rest were "possible". ADRs to zidovudine and nevirapine superseded all others. Interpretation and Conclusion. Gastrointestinal effects were the most commonly observed group of ADRs, with nausea being the most common ADR, the others being gastritis and diarrhoea. The other ADRs included rash, hepatotoxicity, blood dyscrasias like anaemia, neutropenia, and thrombocytopenia, and fatigue. Few cases of lactic acidosis, peripheral neuropathy, headache, lipoatrophy, and pancreatitis were reported.